Nutritional Status of Children with Chronic Kidney Disease, Upper Egypt - El-Asheer, Osama; Amir, Maram M.; Abdel-Moaz, Abdel-Latif M. Abdel-Moaz; Aboelgheet, Amir M. (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Chronic Kidney Disease (CKD) introduces a unique set of nutritional challenges for the growing and developing child. Maintenance of optimal nutrition plays a key role in the management of children with (CKD) across different stages of CKD, during dialysis and following transplantation. AIM: To assess the nutritional status of children with CKD. METHODS: This is a cross-sectional study carried out on 40 children diagnosed with stage 5 CKD of both sex attending Pediatric Nephrology Unite, University Pediatric Hospital, Upper Egypt. Their age ranged from 2-15 years. Patients were subjected to full history taking including dietary intake, full medical examination including anthropometric measurements, and laboratory investigations including complete blood picture, serum calcium, phosphorus, and serum albumin. RESULTS: Weight was the most affected anthropometric parameter, as 80% of the patients were < 5th percentile. 72.5% of our studied children were stunted, their height was less than 5th percentile. Body mass index (BMI) was normal in only 20% of CKD children, no one was obese and 80% were undernourished. Undernutrition was significantly related to the duration of CKD, male gender, age < 5 years, and low socio-economic state. CONCLUSION: Undernutrition is widely prevalent among children with CKD. Long duration of hemodialysis, young age at presentation, low socio-economic state, and male gender are the main risk factors that threaten the nutritional status of those children.